Carbon blues : cars, catastrophes, and the battle for the environment - Mason, Mike, 1938- (McGill-Queen's University Press, 2020)
"Climate change is the most serious crisis of our time. As history is being written in fire in California and Greece, in the warming waters of the Gulf of Mexico, and in the melting ice of the Arctic and Antarctica, Carbon Blues demystifies current debates on climate change, discussing everything from carbon dioxide increases in the atmosphere caused by cars, coal, and oil to global warming and worsening natural disasters. A detailed examination of the history of climate change and its present and future consequences, Carbon Blues traces the essential economic importance of coal in the nineteenth century and oil in the twentieth, emphasizing the role of the automobile and the internal combustion engine in the dereliction of our planet. Exposing campaigns to mislead the public, Mike Mason reveals that the fatal consequences of CO2 and NO2 have been widely known for decades but successfully discounted and manipulated by the carbon lobby led by Exxon, BP, figures such as the Koch brothers, and democratically-elected governments. The book underlines the disturbing truth: that despite current attempts to remediate climate change, the harm already done to melting polar ice and the warming and rising of the seas will be virtually irreversible. As the fight to reverse climate change comes to a head, Carbon Blues searches for fruitful ways forward."--